2008
DOI: 10.1016/j.yhbeh.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Focused grooming networks and stress alleviation in wild female baboons

Abstract: We examine the relationship between glucocorticoid (GC) levels and grooming behavior in wild female baboons during a period of instability in the alpha male rank position. All females' GC levels rose significantly at the onset of the unstable period, though levels in females who were at lower risk of infanticide began to decrease sooner in the following weeks. Three factors suggest that females relied on a focused grooming network as a coping mechanism to alleviate stress. First, all females' grooming networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
221
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(232 citation statements)
references
References 47 publications
9
221
1
1
Order By: Relevance
“…This approach led us to a unique view of agonistic relationships, namely, that they are somehow beneficial. Previous studies linking social bonds and reproductive success have primarily focused on affiliative interactions (2), because such relationships have more immediate and obvious benefits [e.g., reduced stress (31,32), enhanced immune competence (33)]. However, we found that the extent to which a marmot is integrated and centrally positioned in its agonistic network positively covaries with LRS and longevity.…”
Section: Discussionmentioning
confidence: 50%
“…This approach led us to a unique view of agonistic relationships, namely, that they are somehow beneficial. Previous studies linking social bonds and reproductive success have primarily focused on affiliative interactions (2), because such relationships have more immediate and obvious benefits [e.g., reduced stress (31,32), enhanced immune competence (33)]. However, we found that the extent to which a marmot is integrated and centrally positioned in its agonistic network positively covaries with LRS and longevity.…”
Section: Discussionmentioning
confidence: 50%
“…This study showed that Adele penguins treated with high dose GCs (within the stress‐induced range) subsequently increased their affiliative (nonsexual pair‐bonding) behavior (Thierry, Brajon, SpĂ©e, & Raclot, 2014). However, instability in primate social groups (e.g., unstable dominance hierarchy) that is known to elevate GCs in group members (Creel, Dantzer, Goymann, & Rubenstein, 2013) did not affect the amount of nonsexual bonding behavior but was associated with same amount of bonding behavior (grooming) being focused to fewer group recipients (Crockford, Wittig, Whitten, Seyfarth, & Cheney, 2008; Wittig et al., 2008). …”
Section: Evidence That Variation In Stress Physiology Is Associated Wmentioning
confidence: 99%
“…On the other hand, chronic stress may also have opposite effects, tying social groups together. For example, exposure to chronic stress is known to tighten social networks, which results in cooperative or affiliative behavior limited more strictly to a group of close relatives or allies (humans: Dunbar & Spoors, 1995; Kornienko, Clemans, Out, & Granger, 2014; in other species: Zhou, Sornette, Hill, & Dunbar, 2005; baboons: Crockford et al., 2008; Wittig et al., 2008). Consequently, chronic stress may promote in‐group cooperation but also out‐group aggression (Puurtinen, Heap, & Mappes, 2014).…”
Section: Evidence That Variation In Stress Physiology Is Associated Wmentioning
confidence: 99%
“…If aggression reduces female fecundity and a counterstrategy involves long-term stable social relationships between females, the formation of affiliative social bonds may be an adaptive strategy. Also, affiliative social interactions have immediate benefits to individuals, such as reduced heart rate in horses (7), reduced stress in guinea pigs and baboons (8,9), and enhanced immune competence in macaques (10). Therefore, affiliative relationships could have profound impacts on fitness.…”
mentioning
confidence: 99%